Lecturer Assistance Strategies In Optimizing Community Service Programs By Kpm Stain Meulaboh Students Lecturer Assistance Strategies In Optimizing Community Service Programs By KPM STAIN Meulaboh Students - Efendi, Sumardi; Fauza, Muflihatul; Iqbal, Muhammad; Ramli, Ramli; SH, Hendra; Zulhendra, Danil; Ananda, M. Aditya (Malik Al-Shalih : Jurnal Pengabdian Masyarakat, 2025)
The Community Service Lecture Program (KPM) is an integral part of the Tri Dharma of Higher Education which aims to foster social awareness and develop students' capacity in empowering the community. However, the effectiveness of its implementation is often constrained by the lack of systematic mentoring strategies from the supervising lecturers. This study aims to analyze the lecturer mentoring strategy in optimizing the implementation of the community service program by KPM STAIN Meulaboh students. The method used is descriptive qualitative with a participatory approach, through observation, interviews, and documentation of student and supervising lecturer activities. The results of the study indicate that mentoring carried out actively, participatively, and in a directed manner can improve the quality of program planning, implementation, and evaluation by students. Students who receive intensive mentoring show better abilities in identifying community needs, designing programs based on local potential, and establishing effective collaboration with village stakeholders. The mentoring strategy also contributes to shaping students' character as agents of social change. It can be concluded that the active involvement of lecturers in all stages of KPM is the key to the success of impactful and sustainable service.